2022
DOI: 10.1001/jamaneurol.2022.1621
|View full text |Cite
|
Sign up to set email alerts
|

Structural Inequities for Historically Underserved Communities in the Adoption of Stroke Certification in the United States

Abstract: IMPORTANCE Stroke centers are associated with better outcomes. There is substantial literature surrounding disparities in stroke outcomes for underserved populations. However, the existing literature has focused primarily on discrimination at the individual or institutional level, and studies of structural discrimination in stroke care are scant.OBJECTIVE To examine differences in hospitals' likelihood of adopting stroke care certification between historically underserved and general communities. DESIGN, SETTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 80 publications
0
22
0
Order By: Relevance
“…Given the highly technical and interdisciplinary nature of thrombectomy care, the benefit of specialized and certified stroke center care is likely to be even greater in the modern thrombectomy era where shorter time to treatment is associated with better outcomes. We found that a substantial proportion of hospitals treating patients with AIS are not stroke-certified by leading certifying organizations even though overall stroke certification has grown 83.5% from 2009 to 2019 18…”
Section: Discussionmentioning
confidence: 91%
“…Given the highly technical and interdisciplinary nature of thrombectomy care, the benefit of specialized and certified stroke center care is likely to be even greater in the modern thrombectomy era where shorter time to treatment is associated with better outcomes. We found that a substantial proportion of hospitals treating patients with AIS are not stroke-certified by leading certifying organizations even though overall stroke certification has grown 83.5% from 2009 to 2019 18…”
Section: Discussionmentioning
confidence: 91%
“…50 Further differences exist between certified stroke centers and nonstroke centers; hospitals certified as stroke centers tend to be located in higher income service areas, have higher profit margins, and are less likely to be located in rural areas, demonstrating the impact of economic characteristics of patient populations on certification. 54,55 Finally, globally, stroke center certification is more established in highincome countries and regions compared with low-and middle-income countries. 56,57 Integration of Prehospital and Hospital Data Timely feedback is a vital part of continuously improving diagnostic skills and treatment decisions; yet this is uncommonly and inconsistently delivered to frontline EMS practitioners.…”
Section: Structural Components In Prehospital Stroke Systems Of Care ...mentioning
confidence: 99%
“…Hospitals in rural and poorer communities are less likely to become stroke centers, 6 urban hospitals serving racial and ethnic minority communities and rural hospitals have disproportionately closed, and safety net hospitals are also more likely to close their EDs or close entirely. 7 The impact of these closures on stroke care has not been quantified, but they are likely driving widening disparities in stroke outcomes given the timesensitive nature of reperfusion and differential loss of stroke care in vulnerable communities.…”
Section: Hospital and Ed Closures And 2 New Types Of Edmentioning
confidence: 99%